The Impact of Implementing Tax Collection by Forced Letter on Taxpayers In The 18th Residance Establishment Management Agency - Elda Sagitarius; Siti Nuridah (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the impact of tax collection with a Forced Letter carried out by KPP Pratama Dua on taxpayers of the 18th Residence Management Agency (PPRS) The 18th Residence Management Agency in 2020, to determine the impact and efforts made by the 18th Residance Management Agency PPRS In responding to the forced letter, knowing that tax collection through a forced letter can optimize state revenue from the taxation sector for the disbursement of tax arrears. The research method used is qualitative, data collection uses primary data by conducting interviews with competent informants, namely the Financial Supervision of PPRS The 18th Residance Management Agency and observation of research objects PPRS The 18th Residance Management Agency located at Taman Rasuna Said Apartment, tower 18th Kuningan Jakarta South. The research results obtained in this study are that the PPRS The 18th Residance Management Agency has not carried out tax obligations in accordance with generally accepted tax regulations and with efforts to collect taxes through forced letters can optimize in detecting taxpayers who have not and do not carry out tax obligations.